IMPLEMENTASI NILAI TRI HITA KARANA DALAM PENGUATAN KARAKTER DAN KOMPETENSI ABAD KE-21: STUDI KASUS DI SMP NEGERI 2 TABANAN - Paramitasari, Putu Nurcita; Triwijaya, I Nyoman Agus; Agung, Anak Agung Gede (Jurnal Administrasi Pendidikan Indonesia, 2025)
This study aims to analyze the implementation strategies of the Tri Hita Karana values in strengthening students, character and 21st-century competencies at SMP Negeri 2 Tabanan. The research employed a qualitative method with a descriptive-analytic approach by collecting data through observation, interviews, and documentation within the school environment. The findings revealed that the values of Tri Hita Karana, which include Parahyangan (spiritual), Pawongan (social), and Palemahan (environmental), have been systematically implemented through intracurricular, cocurricular, and school culture programs. The integration of these values has significantly contributed to fostering students’ religious character, social harmony, environmental awareness, and adaptive abilities, as well as enhancing their academic and non-academic competencies to meet 21st-century demands. The key supporting factors include strong stakeholder commitment and adequate school facilities, while the main challenges are related to globalization influences and teachers’ workload. The study concludes that the implementation of Tri Hita Karana values effectively cultivates students with strong character, adaptability to change, and 21st-century competencies encompassing critical thinking, collaboration, communication, and creativity skills. The study recommends continuous collaboration among stakeholders to optimize the integration of local wisdom values within the national education system.